PENERAPAN PADUAN MODEL PEMBELAJARAN LEARNING CYCLE DENGAN GROUP INVESTIGATION UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR KIMIA - Maya Istyadji (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract. Effectiveness of learning cycle instructional model in group investigation setting to improve process quality and learning outcome was investigated. This quasi-experimental study involved students of class X SMAN 1 Banjarbaru of South Kalimantan as a subject. Test instruments were used for measuring students comprehension, learning outcome and concept retension. By using anava, LSD and t-test analysis, this study shows that (1) the quality of learning process in learning cycle- group investigation class (LCGI) is able to create situation where the student learning experience can be tranferred to other students, increased analysis ability and explored students ideas (2) there is significant difference of learning outcome between LCGI and conventional instructional model, and no difference between LC and LCGI (3) LC model and LCGI resulted gain score significantly differ to the conventional model, and gain score of LCGI significanly differs to the LC. Futher more, the LC/LCGI increased the students critical think.Key words: learning cycle, group investigation and retention